Phytochemical Evaluation and Combination Effect of the Crude Methanol Extract of Ochna rhizomatosa with Standard drugs - Habila , J. D.; Adeyemi, M. M.; Iyun, O. R. A.; Paul , S. E.; Habila , A. J.; Mohammed , M. I. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
In our search for plants with antimicrobial activities, Ochna rhizomatosa a plant used in the treatment of typhoid fever in Nigerian folk medicine was investigated. The phytochemical investigation of the extract shows the presence of alkaloids, flavonoids, fatty acid and triterpenes. The results of antimicrobial assay on Samonella typhi, two resistant bacteria (Methicillin Resistance Staphyloccocus aureous (MRSA); Vancomycin Resistance Staphyloccocus aureous (VRSA)) and Candida albican expressed in terms of mean diameter of zones of inhibition (mm), shows that the leaves extract (LOS1) inhibited MRSA with a clear zone of 28.00 ± 0.20 mm. Whereas the stem bark (SOS1) shows a zone of 18.00 ± 0.50 mm at 100 mg/ml respectively. The combination of LOS1(100 mg/ml) with Ciprofloxacin (5 ?g/ml), led to enhancement of the measured zone of inhibition (46.00± 0.25 mm). The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) results of the synergistic evaluation of LOS1 with Ciprofloxacin, reveals an enhancement of the inhibition (MRSA, MIC = 3.13 mg/ml) and bactericidal properties (MRSA, MIC = 3.13 mg/ml, MBC = 6.25 mg/ml). These showed that the standard drugs in combination with the extract from Ochna rhimatoza are potentials for the search for treatment for resistant bacteria.